Willingness to counsel HIV Pre-exposure prophylaxis to clients among pharmacists: a systematic review - Nor Hanizah Abdul Gapal; Ummi Ainaa Selamat; Tarmizi Che Ali; Arini Dahlia Saadudin; Selvandiran Ilanchelian; Rafdzah Ahmad Zaki (Penerbit Universiti Kebangsaan Malaysia, 2024)
The successful implementation of PrEP as a prevention program is also associated with the willingness of the healthcare provider to counsel, especially among the pharmacists. We aimed to summarize and synthesize the evidence on level of willingness to counsel HIV Pre-exposure prophylaxis (PrEP) clients among pharmacists for the past ten years. We conducted a systematic search to assess the level of willingness to counsel HIV Pre-exposure prophylaxis (PrEP) clients from five databases; PubMed, SagePub, Science Direct, Web of Science (WOS), and Springer in May 2023. The eligibility criteria are cross- sectional study designs, published in English language, availability of full-text articles, and articles published before the year 2014. The Quality of all seven articles was assessed using Joanna Briggs Institute checklist for Analytical Cross-sectional studies. The results of each study were recorded in the data extraction form. Of an initial 474 potential studies identified, 7 cross-sectional studies met the inclusion criteria. Five out of seven studies showed that willingness among pharmacists to counsel HIV PrEP is more than 50%. Four studies concluded that willingness among pharmacists are influenced by level of knowledge and experience in HIV and PrEP counselling The review adds new evidence about the level of willingness among pharmacists to counsel clients for HIV pre-exposure prophylaxis. However, due to limited high quality studies, the findings are inconclusive.